Comprehending Polysemous Words in Context: A Mixed-Methods Study of EFL Students' Performance, Difficulties, and Comprehension Strategies - Rita Erlinda; Anggun Fatimah Zahra; Martin Kustati (SALEE: Study of Applied Linguistics and English Education, 2026)
This study investigated Indonesian senior high school EFL students' performance in comprehending polysemous words in context, the difficulties they encountered, and the strategies they employed to infer contextually appropriate meanings. An explanatory sequential mixed-methods design was adopted involving 107 eleventh-grade students. Quantitative data were collected through a 28-item contextual polysemous vocabulary test developed from authentic contexts found in two official English textbooks, Bahasa Inggris for Change and Bahasa Inggris Tingkat Lanjut. Qualitative data were subsequently obtained through semi-structured interviews with students representing high, moderate, and low-performing groups to explain the quantitative findings. The quantitative results showed that students demonstrated moderate overall performance (M = 60.15), with 47.7% of the participants categorized as low and very low performers. Item-level analysis revealed considerable variation in students' comprehension across individual polysemous words. Based on the types of polysemy, students showed slightly better performance on regular than on irregular polysemous words. Nevertheless, the difference was not statistically significant (p = .056), indicating comparable comprehension across the two types of polysemy. The qualitative findings identified five major sources of difficulty: unfamiliarity with polysemous words, overreliance on dominant meanings, first language interference, limited exposure to multiple meanings, and difficulty distinguishing semantic nuances among answer options. Students employed five principal strategies to overcome these challenges: dictionary use, context analysis, pair discussion, answer-choice analysis, and guessing, with dictionary use emerging as the most frequently reported strategy. These findings underscore the importance of explicit instruction on polysemy and contextual meaning inference to strengthen students' semantic competence and vocabulary learning in EFL classrooms.